ANALYSIS OF THE MEANING OF ATA PE’ANG KO ATA ONE IN MANGGARAI CULTURE (TRADITION) - Sirilus Ligu (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2016)
Manggarai is an ethnic group who lived in the west side of Flores islands. As an ethnic group they have custom which was certainly precious and inheritance from generation to generation. At traditional ceremonies they used Manggarai language (tombo manggarai) and there are so many terms contained in the language. One of the terms which was inheritance of the Manggarai accentors and thrive in the life of Manggarai society was ata pe’ang ko ata one. The research used of qualitative method. Meaning was of essential concerned to the qualitative. The aim of this study here was to investigate the meaning of social phenomena as experienced by the people themselves. Most of the data in this study got by using interview between researcher and informants and in validity of data the researcher used data triangulation and methodological triangulation. The resulted of the study; the term of ata pe’ang-ata one, still close related to the status of authority in managed the household, the genes, and the rights of ownership. Ata pe’ang-ata one was symbolism language which used when a baby birth in Manggarai socitey. Ata pe’ang (outsiders) was symbol to infants who sex female while ata one (insiders) was symbol to infants who sex male. Along with development of the era, traditional ceremony at the moment that baby birth inch by inch not used by Manggarai society. The researcher suggests that this study can be used as an example in pragmatic, meaning and semiotic and in order to this research to develop theory about pragmatic, meaning and semiotic. In practical the researcher suggests to the English students, lecturer, and further researcher in order that will be using this study as a reference and the study also can upgrade their knowledge.